Les politiques de l’Union européenne pour la conservation-restauration du patrimoine culturel - Clément Serain (In Situ)
The European cultural heritage raises a very particular awareness from the European Union institutions because of its multidisciplinary aspect which places it at the crossroads of many common policies and because of its potential capacity to create a sense of belonging of an entity shared by more than 500 million people. In this context, the material conservation of this heritage appears self-evident. From that point of view, this article focuses on the means used by the European Union to guarantee the conservation and the restoration of its heritage. The aim is twofold: establish an overview of the global legislation and funds allocated to conservation-restoration, and to question, in the context of the culture and heritage policies, the relationship between the European Union and the materiality of its heritage.